UJI AKTIVITAS ANTIOKSIDAN EKSTRAK Gracilaria gracilisDARI VARIASI SUHU DAN WAKTU DENGAN METODEULTRASONIK - Diva Fadhilah (2023)
Gracilaria gracilis is a type of red algae that is widely used in the biotechnology industry as a source of agar and agarose because it has compounds that are useful as antioxidants. Antioxidants play an important role in neutralizing free radicals in the human body so that they can slow down the auto-oxidation process. The ultrasonic extraction method is based on temperature and time so that it can affect the resulting compounds. This study aims to determine the effect of temperature and time variations on the yield value and antioxidant activity of Gracilaria gracilis using the ultrasonic method. The method used was sonication extraction using methanol solvent with a ratio of 1:10 w/v at 50°C, 60°C and 70°C for 25 minutes, 30 minutes and 35 minutes. Extraction results will be tested for antioxidant activity using DPPH. The results of this study showed that the best yield temperature 50°C for 35 minutes and the best total flavonoid content temperature 60°C for 25 minutes had potential antioxidant activity with IC50 values of 1753,65 ppm and 1814,181 ppm.